2010
DOI: 10.1111/j.1467-7660.2010.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Rude Accountability: Informal Pressures on Frontline Bureaucrats in Bangladesh

Abstract: This article is about ‘rude’ forms of accountability — the informal pressures used by citizens to claim public services and to sanction service failures. Rude accountability is characterized by a lack of official rules or formal basis and a reliance on the power of social norms and rules to influence and sanction official performance. The article draws on evidence from Bangladesh, a state which has not reformed its social sector governance, to explore when and why poor citizens resort to ‘rude’ accountability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…The study found higher levels of public goods provision in villages where solidarity groups that were 'encompassing' (open to everyone) and 'embedded' (incorporate local officials) were able to make local officials hold to their public obligations through informal sanction. Hossain (2010) reaches similar conclusions from a study in Bangladesh. She highlights that 'rude' forms of accountability -or forms of accountability that depend on the power of social norms and rules to influence and sanction official performance -were particularly salient because of the prestige and financial incentives associated with holding public office in the country.…”
Section: Top-down 'Versus' Bottom-up Accountabilitysupporting
confidence: 85%
“…The study found higher levels of public goods provision in villages where solidarity groups that were 'encompassing' (open to everyone) and 'embedded' (incorporate local officials) were able to make local officials hold to their public obligations through informal sanction. Hossain (2010) reaches similar conclusions from a study in Bangladesh. She highlights that 'rude' forms of accountability -or forms of accountability that depend on the power of social norms and rules to influence and sanction official performance -were particularly salient because of the prestige and financial incentives associated with holding public office in the country.…”
Section: Top-down 'Versus' Bottom-up Accountabilitysupporting
confidence: 85%
“…But while the role of top-down accountability comes out strongly in Rwanda and Ghana, in other cases there is evidence that a combination of top-down and bottom-up accountability can drive progress, as in Indonesia, where they worked in tandem but to different effect. The case studies therefore support the move in wider literature towards examining top-down and bottom-up accountability as complementary as opposed to being an 'either or' proposition (Joshi 2012).The cases also illustrate findings made elsewhere that pro-poor service provision might occur where forms of social accountability draw on moral reciprocity, are locally grounded, and build on a culture of participation (Booth 2011a;Hickey 2006;Hossain 2010). For example, the accountability of local leaders in the health sector in Bangladesh depended on the extent to which those leaders were 'embedded' in local networks of relationships between local authorities, citizen groups, and service providers.…”
supporting
confidence: 59%
“…The cases also illustrate findings made elsewhere that pro-poor service provision might occur where forms of social accountability draw on moral reciprocity, are locally grounded, and build on a culture of participation (Booth 2011a;Hickey 2006;Hossain 2010). For example, the accountability of local leaders in the health sector in Bangladesh depended on the extent to which those leaders were 'embedded' in local networks of relationships between local authorities, citizen groups, and service providers.…”
Section: Top-down Control and Embedded Accountabilitymentioning
confidence: 70%
“…Evidence emerging from Africa is also disappointing (Bland, 2011;Booth, 2011;Gaventa & McGee, 2010;. 8 Even two impressive accounts of informal, bottom-up accountability concede that it is at best a weak substitute for properly functioning formal accountability (Hossain, 2010;Tsai, 2007: 371).…”
Section: Control and Voice In Service Deliverymentioning
confidence: 99%